The role of tranexamic acid in breast and body contouring surgery: a review of the literature - Daniel Wong; Tai K 'Quoc' Lam (Australasian Journal of Plastic Surgery)
**Background**: Postoperative seroma and haematoma are two of the most common complications follow-ing large surface area surgeries. A review of the literature was performed to evaluate evidence for the use of tranexamic acid in reducing postoperative seroma and haematoma formation in breast surgery and body contouring surgery.